2021
DOI: 10.3329/ptcb.v31i1.54109
|View full text |Cite
|
Sign up to set email alerts
|

An Improved liquid Culture System for Efficient Shoot Multiplication in Aerva lanata (L.) Juss. Ex Schult.

Abstract: An improved in vitro mass propagation protocol was developed for Aerva lanata using MS liquid medium. The influence of MS medium (solid and liquid) with cytokinin (TDZ and BAP, respectively) were studied for shoot proliferation and growth. The liquid medium perfomed better than solid medium in shoot multiplication. The maximum shoot multiplication rate was (29.37 ± 0.64 shoots per explant), obtained in MS liquid medium which is containing 0.6 mg/l TDZ, 0.3 mg/l NAA and 0.2 mg/l IBA. Different volumes of liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Similarly, successful production of Jatropha curcas (Singh, 2018), Dendrocalamus longispathus (Borpuzari & Bisht, 2018), Vaccinium vitisidaea ssp. minus (Arigundam et al, 2020) and Aerva lanata (Varutharaju et al, 2021) have been reported under tissue culture conditions using liquid culture media. Shoot lengths in nutrient solutions with ZEA + IAA are given in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, successful production of Jatropha curcas (Singh, 2018), Dendrocalamus longispathus (Borpuzari & Bisht, 2018), Vaccinium vitisidaea ssp. minus (Arigundam et al, 2020) and Aerva lanata (Varutharaju et al, 2021) have been reported under tissue culture conditions using liquid culture media. Shoot lengths in nutrient solutions with ZEA + IAA are given in Figure 4.…”
Section: Resultsmentioning
confidence: 99%